Direction of Policy Convergence in the EU: The Case of Genetically Modified Maize Labelling Policies - Gustavo Sadot Sosa-Núñez (Romanian Journal of European Affairs)
The aim of this article is to contribute to the academic dialogue of policy convergence by examining the direction taken by the policy to label genetically modified maize in the European Union. Considering international harmonisation as the causal mechanism, this article provides a chronological account of policy outputs, understood as directives and regulations related to this policy area. Additionally, there is an analysis of the increase of the degree of policy convergence. Furthermore, different national perspectives on the issue are presented, offering an insight about policy direction in terms of the interaction that governments of member states have between them and with the European Commission. Concomitantly, the direction that policy convergence takes points at strengthening member states’ views of developing stricter rules through time. Subsequently, results demonstrate that policy convergence can appear only with member states’ consent, regardless of the position that regional institutions may have; although they may influence the process to some extent. Nonetheless, this does not mean that the current direction should be taken for granted.